The Relationship Between Organizational Culture And Employee Performance At The Directorate Of P2humas, DJP Jakarta - Hersanius Kurnia Peong; Eugenius Besli; Andy Iwan Iswanto (Pusat Penelitian dan Pengabdian Masyarakat Politeknik eLBajo Commodus, 2024)
Organizational culture plays an important role in supporting organizational performance to achieve the vision, mission and goals of the organization. Good management is the key to the success of organizations such as the Directorate of Counseling, Services and Public Relations (Dit. P2Humas) of the Directorate General of Taxes (DGT) to achieve good organizational implementation and achieve the set work targets. Therefore, this study aims to review the implementation of organizational culture in developing employee performance at DGT. P2Humas. The method used is descriptive qualitative method, which is descriptive in nature by conducting a study based on theory and previous research, and data collection is carried out using the interview method, and direct observation of employees at DGT. P2Humas. Qualitative data analysis uses the Miles and Hubermans model which consists of data reduction, data presentation, and conclusion drawing/verification. Data validity was tested using triangulation techniques and source triangulation. The results of this study explain that Dit. P2Humas has implemented organizational culture (values of the Ministry of Finance and the Directorate General of Taxes Code of Ethics) well. The practice of this organizational behavior has a positive effect on the development of employee performance which is a reflection of the practice of organizational culture. If the process of internalizing organizational culture into personal culture has been successfully carried out, employees will be integrated with the organization and there will be no obstacles to achieving optimal organizational goals.